2012
DOI: 10.1017/s026646741200020x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclone Aila on estuarine fish assemblages in the Matla River of the Indian Sundarbans

Abstract: Abstract:The present study examined the effect of a catastrophic cyclone (Aila) on ichthyofaunal assemblages in a tidal river of the Sundarban Delta. Sampling in six stations with a gill-net of 20-m length and 1-cm mesh size resulted in the collection of 63 species in a pre-Aila survey. Among them, 16 species were not available in the year after the cyclone. However, 12 new species were added to the assemblages in the post-Aila year during which 59 species were recorded. Analysis of Similarity (ANOSIM) confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…It claimed 138 human lives, killed numerous cattle and destroyed human properties 36 , 37 . Thus far, scientific studies conducted to portray the aftermath of the cyclone have mostly dealt with ecological 35 , 38 and economical effects 39 , livelihood and resilience 40 , post disaster health hazards like diarrhea and cholera outbreaks 41 43 and the psychological impacts on the adult population 44 . However, according to our knowledge, no study, so far, considered growth, development and physical characteristics of children exposed to the PNMS and early postnatal distress due to Aila .…”
Section: Introductionmentioning
confidence: 99%
“…It claimed 138 human lives, killed numerous cattle and destroyed human properties 36 , 37 . Thus far, scientific studies conducted to portray the aftermath of the cyclone have mostly dealt with ecological 35 , 38 and economical effects 39 , livelihood and resilience 40 , post disaster health hazards like diarrhea and cholera outbreaks 41 43 and the psychological impacts on the adult population 44 . However, according to our knowledge, no study, so far, considered growth, development and physical characteristics of children exposed to the PNMS and early postnatal distress due to Aila .…”
Section: Introductionmentioning
confidence: 99%
“…The pelagic communities of river-estuaries generally recover soon after TCs because disruptions are often mechanical and are forced by oods which proceed TCs (Cheal et al 2002;Peierls et al 2003;Mukherjee et al 2012;Paul et al 2020a;Liu et al 2021). If the abiotic conditions of the habitat change drastically after a TC and remained so for a considerable period then that poses a challenge for populations to recolonize the habitat, which happened after TC Aila (May 2009) in Indian Sundarbans (Mukherjee et al 2012;Bhattacharya et al 2014). Shortly after Amphan, Muriganga turned to a warm, polyhaline and alkaline (pH > 8) habitat and such a condition lasted for a few weeks; however, that is not unusual for Muriganga specially in late PRM to early MON because evaporation rates remain high in that period due to high ambient temperature (Mukhopadhyay et al 2006).…”
Section: Abiotic Variability Of Murigangamentioning
confidence: 99%
“…With the advancement of weather forecasting, tracking TCs before their land fall have become more predictable than 20th Century (Madsen and Jakobsen 2004;Mohanti et al 2019); therefore, the estuarine scienti c community is able to conduct before-after assessment of disruptions caused by a TC or successive TCs (Steinke and Ward 1989;Pearl et al 2001;Mukherjee et al 2012;Beyrend-Dur et al 2013;Bhattacharya et al 2014;Kumar et al 2017;Paul et al 2020a). Impacts of hurricanes that hit eastern coasts of North America have received attention in estuarine literatures because biogeochemical cycles and ecological communities a few estuaries are regularly monitored so assessments of before-after cyclonic disruptions are possible (Gong et al 2007;Wetz and Pearl 2008;Pearl et al 2018;Phlips et al 2020;Wachnicka et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hurricanes can cause significant destruction to coral reefs, with corresponding changes in the reef fish population (Woodley et al, 1981). In an estuarine environment, a significant change in fish assemblages was observed after the passage of a cyclone, with reduction in species diversity and variation in the seasonal pattern of abundance (Mukherjee et al, 2012). A satellite tracking study on manatees in southwest Florida showed no significant effect on movement patterns before and during hurricane passages, and it was therefore concluded that the hurricanes had a minor effect on this species (Langtimm et al, 2006).…”
Section: Introductionmentioning
confidence: 99%